One root is square of the other root of the equation , then the relation between and is?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The two roots satisfy:
x = 2 − p ± ( p 2 − 4 q ) ;
and if one root is the square of the other, then we obtain:
2 − p + ( p 2 − 4 q ) = ( 2 − p − ( p 2 − 4 q ) ) 2 ⇒ 2 − p + ( p 2 − 4 q ) = 4 p 2 + 2 p ∗ ( p 2 − 4 q ) + ( p 2 − 4 q ) ;
or 2 − p + ( p 2 − 4 q ) = 4 2 p 2 + 2 p ∗ ( p 2 − 4 q ) − 4 q ) ;
or 2 ∗ [ − p + ( p 2 − 4 q ) ] = 2 p 2 + 2 p ∗ ( p 2 − 4 q ) − 4 q ;
or ( 2 − 2 p ) ( p 2 − 4 q ) = 2 p 2 + 2 p − 4 q ;
or 4 ( 1 − 2 p + p 2 ) ∗ ( p 2 − 4 q ) = ( 2 p 2 + 2 p − 4 q ) 2 ;
or 4 ( p 2 − 2 p 3 + p 4 − 4 q + 8 p q − 4 p 2 q ) = 4 p 4 + 8 p 3 + 4 p 2 − 1 6 p 2 q − 1 6 p q + 1 6 q 2 ;
or 1 6 p 3 − 4 8 p q + 1 6 q 2 + 1 6 q = 0 ;
or p 3 − 3 p q + q 2 + q = 0 ;
or p 3 − q ( 3 p − 1 ) + q 2 = 0 .